Why Do Some Toddlers Help A Stranger? Origins of Individual Differences in Prosocial Behavior. (20th December 2013) - Newton, Emily K.; Goodman, Miranda; Thompson, Ross A.
<x xml:space="preserve">Abstract</x> This study investigated the influence of emotion on toddlers' prosocial behavior in instrumental helping tasks with an unfamiliar adult. The goals were to examine whether early prosocial behavior was affected by (1) the adult's expressions of sadness (in contrast to a neutral expression) as a cue of need and (2) toddlers' emotion understanding. Thirty‐five 18‐ to 20‐month‐olds participated in eight trials in which an experimenter either indicated need for assistance (experimental condition) or did not (control). In addition, the experimenter expressed either sadness or neutral affect in each trial. Toddlers' emotion understanding was assessed using maternal reports of children's emotion words. The experimenter's emotional expression alone was not associated with prosocial behavior, but toddlers helped more in experimental than control conditions. However, toddlers with larger emotion word vocabularies were marginally more prosocial when the experimenter expressed sadness, and girls provided more assistance than boys in experimental conditions. These findings highlight the complex influences of emotion on early prosocial motivation.